2021
DOI: 10.3390/antiox10091478
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Effects of an Early Postpartum Intravenous Infusion with Carnosic Acid on Physiological Responses of Transition Dairy Cows

Abstract: The objective of the present study was to evaluate the effects of an antioxidant and anti-inflammatory compound found in rosemary plants (Salvia rosmarinus) named carnosic acid during the transition period of dairy cows. From day 1 to 3 after calving, 16 multiparous Holstein cows received a daily intravenous infusion of either 500 mL of saline (NaCl 0.9%; Saline; n = 8) or carnosic acid at a rate of 0.3 mg/kg of BW supplied in 500 mL of saline (CA; n = 8). Blood samples were taken at –7, 2, 5, 7, 14, and 21 d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…In our study, RE supplementation decreased the MDA concentration and increased the SOD concentration, indicating that RE improved the oxidant status of dairy cows. Michelotti et al directly infused carnosic into the veins of transition dairy cows and observed a positive effect on inflammation and oxidative stress biomarkers [ 44 ]; the underlying mechanism may involve the activation of the PI3K/AKT/Nrf2 signaling pathway [ 45 , 46 ]. Furthermore, our results indicated that RE supplementation may decrease the SCC in milk.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, RE supplementation decreased the MDA concentration and increased the SOD concentration, indicating that RE improved the oxidant status of dairy cows. Michelotti et al directly infused carnosic into the veins of transition dairy cows and observed a positive effect on inflammation and oxidative stress biomarkers [ 44 ]; the underlying mechanism may involve the activation of the PI3K/AKT/Nrf2 signaling pathway [ 45 , 46 ]. Furthermore, our results indicated that RE supplementation may decrease the SCC in milk.…”
Section: Discussionmentioning
confidence: 99%